The new system of the talent development program in Hungarian soccer - Csaki, I.; Geczi, G.; Kassay, L.; Deri, D.; Revesz, L.; Zalai, D.; Bognar, J. (Biomedical Human Kinetics, 2014)
Study aim: due to a series of failures and the drastic reduction in the quality of Hungarian soccer, greater emphasis should be put on coaches` professional development and talent development programs. The aim of this study was to present the newly established Hungarian Soccer Development Program that focuses on the development of youth talent.